ISSUES IN DESIGNING INSTRUMENT FOR AFFECTIVE ASSESSMENT BASED ON SCIENTIFIC APPROACH: ENGLISH TEACHERS’ REFLECTION - Ira Maisarah (English Language Teaching and Research, 2017)
This research was describing the issues in designing instrument for affective assessment based on scientific approach. It is a reflection of English teachers in assessing the students’ affective in English language teaching. In English language teaching, an English teacher is not only forced to assess the students’ competence on language, but also their affective. Good affective is believed can support the students’ successfulness in learning. That’s why, the English teacher must assess the students’ affective frequently and continuously as an attempt to gain the progresses and the changes of students’ affective during the learning process. But, the English teachers have some problems in designing instrument for affective assessment based on scientific approach. So, it’s become the main issue in doing the evaluation for English classroom. For that reason, the researcher used qualitative method by giving depth interview with the English teachers in Junior High School in order to point out the issues. Moreover, it’s found that: (1) the instrument used by English teachers in assessing affective was still general, not based on phases in the scientific approach; (2) the indicator for scoring affective could not define the specific description for each type of affective; (3) the English teachers focused on one attitude to be assessed; and (4) the instrument used in assessing affective was a blank paper without any instruction, explanation, or table for noting the students’ scores. Finally, it is hoped that the English teachers can develop the instrument based on subject and approach used in English language teaching. Key words/phrases:  Issue, Instrument, Affective Assessment, Scientific Approach, Teachers’ Reflection